Thoracic Origin of Single Right Renal Artery: Some Interesting Facets - Gadabanahalli, Karthik; Bhat, Venkatraman (International Journal of Angiology, 2017)
Two cases of thoracic origin of the right renal artery, arising from the level of D11 vertebrae detected on an incidental computed tomography examination are reported. A brief review of embryology is presented. Simultaneous variation of the origin of the right inferior phrenic artery is highlighted as a unique feature of our cases. The importance of this relatively uncommon anomaly in the clinical context is discussed.
Keywords: single ectopic right renal artery; right inferior phrenic artery; renal artery anomaly; thoracic origin of renal artery; computed tomography angiography